Transformational Leadership and Teacher Work Motivation in the Digital Era: The Mediating Role of Teacher Readiness for Change - Ahmad Rais Habib (International Humanity Advance, Business & Sciences, 2026)
This study analyzes the influence of principals' transformational leadership on teachers' work motivation in the digital era, with readiness for change as an intervening variable. Amidst the increasingly massive demands of digital transformation in education, it is crucial for schools to understand the factors that influence teachers' work motivation to maintain the quality of learning. Data were collected through a survey involving 75 teachers in Enrekang Regency who are facing the dynamics of technology adaptation. The analysis method used was Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), which allows researchers to test the relationship between variables simultaneously. The results show that transformational leadership has a positive and significant influence on teachers' work motivation, and readiness for change acts as a mediator that mediates the relationship between transformational leadership and teachers' work motivation in the digital era. These findings emphasize the importance of enhancing transformational leadership capacity to not only encourage technology adoption but also improve teachers' mental readiness and work motivation.